Economic Reform in Arab Countries : A Review of Structural Issues for the Remainder of the 1990's - El-Erian, Mohamed (IMF Working Papers; Working Paper ;, 1993)
The paper reviews the main structural reform issues facing Arab countries in the remainder of the 1990s. While the nature, extent, and implications of the policy challenges differ among individual countries in the Arab region, several aspects are common to a large number of them. Accordingly, the paper identifies a framework consisting of a core of key reforms that would address these countries' structural weaknesses and assist them in exploiting their considerable economic potential.